Effects of pre- and post-exercise cold-water immersion therapy on passive muscle stiffness - Hüttel, M.; Golditz, T.; Mayer, I.; Heiss, R.; Lutter, C.; Hoppe, M. W.; Engelhardt, M.; Grim, C.; Seehaus, F.; Forst, R.; Hotfiel, T. (Sportverletzung Sportschaden, 2020)
Cold-water immersion (CWI) has become a popular preventive, regenerative and performance-enhancing intervention in various sports. However, its effects on soft tissue, including changes of intramuscular stiffness, are poorly understood. The purpose of this study was to investigate the effect of CWI on muscle stiffness.